RETRACTED: FEM Analysis on Thermo-mechanical behavior and experimental validation of Al20Cr20Fe25Ni25Mn10 High Entropy Alloy during Spark Plasma Sintering - Kanyane Lehlogonolo Rudolf; Popoola Patricia; Mpofu Praise; Malatji Nicholas; Ogbonna Victor (E3S Web of Conferences)
This proceeding volume has been retracted from the publication because we found some solid reasons to believe that it has infringed our integrity criteria and now presents a risk for our journal and scholarly science in general. Different types of malpractice are involved, in particular citation manipulation and inappropriate references. We are extremely concerned by such malpractice which considerably impacts the image of our title and our Publisher’s reputation. For further details, please refer to our publishing ethics policies. If you have any questions, please contact us at contact@webofconferences.org See the retraction notice E3S Web of Conferences 505, 00001 (2024), https://doi.org/10.1051/e3sconf/202450500001